Compression Mechanical Properties and Constitutive Model for Soft–Hard Interlayered Rock Mass - Jinhua Li; Yang Yang; Pan Wang; Tianyu Zhang; Peili Su; Songwei Zhao (Advances in Civil Engineering)
The properties of soft–hard interbedded rock masses are significantly impacted by the strength of rock layers and the characteristics of interface surfaces. This study investigates the mechanical properties of soft–hard interlayered rock masses by preparing rock-like specimens with different interface angles. Uniaxial and triaxial compression tests were conducted to examine the compression mechanical characteristics of the specimens. Experimental results demonstrated that in the uniaxial compression tests, the peak strength of the two-layer rock-like specimen exhibits an initial decrease followed by an increase as the interface angle increases. Similarly, the peak strength of the three-layer rock-like specimen also follows a “U-shaped” pattern. The failure of both specimens shifts from tensile failure to shear failure. In the triaxial tests, the strength of the two-layer rock-like specimen initially increases and subsequently decreases as the interface angle increases. In contrast, the intensity of the three-layer rock-like specimen exhibits a decreasing trend, transitioning from shear dilation or tensile failure to shear failure. By utilizing the damage constitutive model to compute the compressive strength of the composite specimen, it was observed that the deviation from the experimental value did not exceed 2.5%, and the overall shape of the curves was in good agreement. Consequently, it is affirmed that the damage constitutive model developed in this study can accurately capture the pre-peak phase of the stress–strain relationship in soft–hard interlayered rock-like specimens, thus providing a valid representation of their mechanical behavior.